MINING STRATEGY IN INCREASING CHOCOLATE MUSHROOM CULTURE PRODUCTION ON (USAHA MATAHARI JAMUR DI DESA PAROMBEAN KABUPATEN ENREKANG) - Arnelin Anggraini; Agus Syam; Asmayanti; Nur Halim; Andika Isma (CV. ADIBA AISHA AMIRA, 2025)
This research aims to find out the development strategy in increasing the production of cultivation of chocolate squid mushrooms (pada usaha matahari jamur di Desa Parombean Kabupaten Enrekang). The research method used through qualitative descriptive research using methods of data collection through observations, interviews and documentation of an object of research which will then be analyzed using SWOT analysis. Through interviews with stakeholders in the Sun Fungi enterprise in Parombean Village Enrekang district, the conclusion drawn based on the current conditions, the sun fungi business in Parobean village Enrekange district is in the first quarter, showing that the company is experiencing a very favourable situation. The strategy that can be applied to the Sun mushroom enterprise in Parombean Village Enrekang district in terms of Quadrant I is aggressive strategy.